Significance of active screening for detection of health problems in childhood cancer survivors - Yoshimoto-Suzuki, Yuri; Hasegawa, Daisuke; Hosoya, Yosuke; Saito, Go; Nagase, Kyoko; Gunji, Michiyo; Kobayashi, Kyoko; Ishida, Yasushi; Manabe, Atsushi; Ozawa, Miwa (Frontiers in Pediatrics, 2022)
Background: Childhood cancer survivors (CCSs) have a lifelong increased risk of chronic health problems, most of which are associated with the curative therapies. Recent studies have suggested that prospective active screening using comprehensive assessments for CCSs is superior in identifying undiagnosed chronic health problems. Methods: To assess the significance of active screening using comprehensive medical examinations for detecting chronic health problems in multiple organ systems in CCSs, we retrospectively compared the frequency and severity of health problems between two different cohorts of CCSs in a single institution: 110 CCSs who visited the outpatient clinic for regular follow-ups between December 2010 and December 2015 (regular follow-up group) vs. 58 CCSs who underwent comprehensive medical examinations between February 2016 and September 2019 (active screening group). CCSs were defined as patients aged ≥18 years who had been diagnosed as having childhood cancer ≥10 years before and had survived without cancer for ≥5 years. Results: Patient characteristics were similar between the two groups except for primary diagnosis (more brain tumors and embryonal tumors in the active screening group) and treatment history (more alkylating agents used and surgical interventions performed in the active screening group). The prevalence and the median number of health problems were significantly higher in the active screening group than in the regular follow-up group: 93% vs. 67% and 1.0 [0.0–8.0] vs. 2.0 [0.0–7.0] respectively. In term of organ-specific health problems, pulmonary dysfunction, neurocognitive impairment, ocular abnormalities, and dental abnormalities were identified more in the active screening group, partly because these problems had not been assessed in the regular follow-up group. Nevertheless, the prevalence of grade 3–5 health problems was similar between the two groups, except for pulmonary dysfunction. Conclusions: Active screening using comprehensive medical examinations was effective for identifying health problems in CCSs. Although the prevalence of severe problems identified by both approaches was similar, comprehensive medical examinations could detect overlooked problems such as severe pulmonary dysfunction, dental maldevelopment, and borderline intellectual functioning, which might have an impact on quality of life in CCSs.